The Making of Policy: Institutionalized or Not? - Carlos Scartascini; Mariano Tommasi (Inter-American Development Bank (IDB), 2009)
This paper develops a framework for analyzing different policymaking styles, their causes and their consequences in Latin America, finding that lower institutionalization and greater use of alternative political technologies (APTs) are more likely the lower the cost of using these technologies, the higher the potential damage they can cause, the lower the wealth of the economy, and the more asymmetric the distribution of de jure political power. Moreover, strategic complementarity exists in the use of alternative political technologies; for instance bribes by the rich and protests by the poor are likely to be countervailing forces, and will both occur in polities with weaker political institutions.
Keywords: D72; D74; D78; H89; K42; 330; Political institutions; Public policies; Institutional strength; Protests; Alternative Political Technologies; Development; Judicial independence; Party institutionalization; Congress capabilities; Cabinet stability; Corruption